2017
DOI: 10.1016/j.margeo.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory morphodynamic hindcast of the evolution of the abandoned Yellow River delta, 1578–1855 CE

Abstract: The Abandoned Yellow River Delta (AYD), which formed when the Yellow River flowed into the Southern Yellow Sea between 1128 and 1855 AD, is a representative example of the sensitivity of deltas to modifications in their environments. In this study, we established a process-based morphodynamic model to explore the morphological evolution of one such largescale fine-grained delta (the AYD before 1855). The uncertainties in the model settings, which are inevitable when historical data are insufficient, were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 91 publications
(162 reference statements)
1
12
0
1
Order By: Relevance
“…The Jiangsu coast can be divided into two distinct geomorphological zones: the northern Abandoned Yellow River Delta (AYD) and the fan-shaped Radial Sand Ridges (RSR) in the south (Figure 1b). The AYD is a typical river-wave dominated delta that was formed by the large fine-grained sediment load carried by the Yellow river, until the river shifted its course towards the Bohai sea in 1855 AD [64]. Upon abandonment and continuing until the present, the former delta started to erode.…”
Section: The Jiangsu Coast and Tongzhou Baymentioning
confidence: 99%
“…The Jiangsu coast can be divided into two distinct geomorphological zones: the northern Abandoned Yellow River Delta (AYD) and the fan-shaped Radial Sand Ridges (RSR) in the south (Figure 1b). The AYD is a typical river-wave dominated delta that was formed by the large fine-grained sediment load carried by the Yellow river, until the river shifted its course towards the Bohai sea in 1855 AD [64]. Upon abandonment and continuing until the present, the former delta started to erode.…”
Section: The Jiangsu Coast and Tongzhou Baymentioning
confidence: 99%
“…Thus, the model online couples flow and morphology and produces bathymetric change in an up-scaled period. Numerous case studies have demonstrated high capacity of the Delft3D model system on reproducing detailed flow features, sediment dynamics and morphological evolution of coastal and estuarine systems (van der Wegen et al, 2011;Dissanayake et al, 2012;van Maren et al, 2015;Su et al, 2016;Luan et al, 2017).…”
Section: Process-based Morphological Modelingmentioning
confidence: 99%
“…The AHD is a remarkable example of serious coastal erosion. The AHD was formed when the Huanghe flowed into the South Yellow Sea (SYS) during 1128–1855 CE and was abandoned when the Huanghe completely changed its course in 1855 to meet the Bohai Sea (BS) (Su et al., 2017; Zhou et al., 2014). The sediment yield by coastal erosion from the AHD was estimated to be approximately 700–1,000 Mt/yr (Zhou et al., 2014), comparable to the sediment discharge of the Huanghe and larger than that of the Changjiang before its damming (1,080 and 480 Mt/yr, respectively; Milliman & Meade, 1983).…”
Section: Introductionmentioning
confidence: 99%